Sintesis dan Karakterisasi Membran Ramah Lingkungan dari Limbah Styrofoam dengan Penambahan Biochar - Nur Fadhila; Yasmine Nur Rahmawati; Nana Dyah Siswati (Jurnal Serambi Engineering, 2024)
Styrofoam waste is increasingly found in Indonesia as packaging, craft materials, decorations, construction materials, etc. Styrofoam consists of 90-95% polystyrene and 5-10% n-butane gas. The production of membranes is one of the solutions to reduce Styrofoam waste through the phase inference method. Polymer membranes in general have poor physical properties. However, this problem can eventually be overcome by adding blends. The addition of biochar has the potential to improve the compatibility between biochar particles and polystyrene. The membrane fabrication results are compared to determine the variation of biochar addition and thickness that has the best hydrophilic properties until the membrane has a contact angle <90o and high porosity. Based on the results of porosity and contact angle analysis on PS-biochar membrane, the best concentration and thickness ratio for membrane fabrication is 2:28 (%Wt) 0.13 mm thickness with a contact angle value of 79°, which means the membrane is hydrophilic as evidenced by the size of contact angle <90° and porosity of 33%. In the results of FTIR (Fourier Transform Infrared Spectroscopy) analysis on the biochar polystyrene membrane there is a peak absorption wave at 1800 which is the absorption of the C=O group which is the absorption of the functional group of biochar.